The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.2223/jped.1702
|View full text |Cite
|
Sign up to set email alerts
|

An evident view of evidence-based practice in perinatal medicine: absence of evidence is not evidence of absence

Abstract: ResumoObjetivo: Proporcionar elementos valiosos e um pouco de humor nesta chamada era da "prática baseada em evidências" com o objetivo de ajudar os clínicos a fazer escolhas melhores no cuidado que eles provêem com base em evidências, e não simples ou exclusivamente com base em um ensaio clínico randomizado (ECR) ou meta-análise (o que pode não ser evidência). Fontes dos dados:Livros e artigos com revisão por pares são citados e listados na bibliografia. Evidências de vida, aprendizado através de nossos própr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
0
3
0
3
Order By: Relevance
“…In the studies we found that newborn infants on music therapy group showed clinically less variability of all physiological variables during the physiotherapy procedures. A clinical important result cannot always be considered statistically significant 14 . This difference is particularly important considering the procedure performed in the two groups, it is considered invasive 15 .…”
Section: Discussionmentioning
confidence: 99%
“…In the studies we found that newborn infants on music therapy group showed clinically less variability of all physiological variables during the physiotherapy procedures. A clinical important result cannot always be considered statistically significant 14 . This difference is particularly important considering the procedure performed in the two groups, it is considered invasive 15 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to all of the above, it has been identified that good care should not be based solely on the findings of RCTs (15,(26)(27)(28)(50)(51)(52)(53)(57)(58)(59). Acknowledging that evidence may still be misinterpreted or distorted by recalcitrant proponents of entrenched practices and other biases, the authors state that rational, quantitative evidence may not necessarily be the only, or even the main, factor driving healthcare decisions.…”
Section: Brief Comments On the Rctsmentioning
confidence: 99%
“…The correctable weaknesses that still persist in the design, conduct, and analysis of biomedical and public health research studies, produce misleading results and waste valuable resources. Statistical precision is often used in a misleading way, and the arbitrary choice of analyses might affect the reported findings . Unfortunately, consensus building groups and bedside care providers remember the novel findings of some studies, despite significant flaws, when taking care of patients.…”
Section: Brief Comments On the Rctsmentioning
confidence: 99%
“…Apesar de as variáveis estudadas terem apresentado significância estatística em alguns dos momentos avaliados, todos os valores permaneceram em intervalos considerados fisiológicos. Contudo, a não-equivalência da significância estatística e da importância clínica destes resultados deve ser considerada criteriosamente; um resultado significativo estatisticamente muitas vezes pode não ser considerado clinicamente importante, assim como é verdadeiro o inverso (28) . Desta forma, torna-se imprescindível que o papel do fisioterapeuta dentro das unidades neonatais seja reformulado, deixando de ser somente o profissional que aplica técnicas para a manutenção da higiene brônquica e passe a ser também o profissional que pesquise e questione o real valor da fisioterapia respiratória, procurando respostas para questões como: em que situações clínicas os recursos de fisioterapia podem ser deletérios?…”
Section: Discussionunclassified